Clinical significance of aortic arch plaques simultaneously assessed with coronary atherosclerosis on cardiovascular outcomes in patients undergoing coronary CT angiography. (14th October 2021) - Otsuka, K; Ishikawa, H; Kono, Y; Shirasawa, K; Hirata, K; Kasayuki, N
Abstract: Aims: Computed tomography (CT) coronary angiography is a useful diagnostic imaging modality in assessing presence, severity, and extent of coronary artery disease (CAD). Aortic arch plaques have been shown to be an underlying cause of embolic stroke and also related to increased risk of cardiovascular events. Yet, conventional CTCA imaging protocol does not include aortic arch for the reduction of radiation exposure. This study aimed to investigate prevalence of aortic arch plaques simultaneously assessed by CTCA and their clinical significance in combination with the presence of obstructive CAD for prediction of CVD events in patients with suspected CAD. Methods: This study consisted of 310 (mean age, 66 years old, 42% female) patients with suspected CAD undergoing CTCA between 2017 and 2019. All CTCA examination was performed with 320-row detector scanner using ECG-triggered prospective gating method. Aortic arch images were simultaneously acquired during CTCA scanning without an increase of contrast media. Using Agatston method, coronary artery calcium score (CACS) was categorized into either of the groups having CACS of 0, 0–99, 100–299, or more than 300. The presence of CAD was reported as non-obstructive or obstructive CAD. High-risk featured aortic plaque was defined as large plaques >4 mm in thickness showing ulceration or protrusion. A composite event of cardiovascular disease, including all-cause mortality, non-fatal myocardial infarction, unplanned hospitalization requiring revascularization or stroke was defined as the primary endpoint. Results: Patients having CACS of 0, 0–99, 100–299, and >300 were found in 41%, 24%, 15%, 20%%, respectively, where obstructive CAD was diagnosed in 11%. Aortic HRPs in ascending aorta, aortic arch, and thoracic descending aorta were observed in 1.6%, 6.9%, and 15%, respectively. During a mean follow-up period of 2.2 years, the primary endpoint was observed in 27 patients (8.7%). Cox regression hazard model demonstrated an independent association of aortic arch high-risk plaques (HR; 3.2, 95% CI; 1.20–8.64, p=0.02) and obstructive CAD (HR; 3.3, 95% CI; 1.45–7.92, P=0.005) when adjusted by age, CACS, and chronic kidney disease. Kaplan-Meier curve analysis showed a worse outcome of patients with aortic HRP and obstructive CAD compared to those without aortic plaques and obstructive CAD (p<0.001). Conclusion: This study demonstrated an independent association of aortic arch high-risk featured plaques with CVD events. Further study is warranted whether pharmacological interventional therapies can reduce future CVD risks in patients with CAD and aortic arch plaques. Funding Acknowledgement: Type of funding sources: None.